Realization of the digital to analog converter for model of the voltage in network - Goncharova O.A. (Научно-технический вестник Брянского государственного университета)
The article discusses the disadvantages of digital measuring instruments. Formulated the task of modeling the measuring device for different waveforms and measurements with the use of microcomputers. Studied and selected mathematical models to describe the behavior of measuring instruments and for different waveforms. Modeled amperage characteristics of a simple electrical circuit to check the correctness of the choice and implementation of the models. Implemented a program of virtual simulation for signals of different forms. The program allows measurements regardless of the waveform that is a distinctive feature of the developed program.